A BRIEF COGNITIVE‐BEHAVIORAL INTERVENTION FOR TREATING DEPRESSION AND PANIC DISORDER IN PATIENTS WITH NONCARDIAC CHEST PAIN: A 24‐WEEK RANDOMIZED CONTROLLED TRIAL. Issue 7 (26th April 2013) - van Beek, M.H.C.T.; Oude Voshaar, R.C.; Beek, A.M.; van Zijderveld, G.A.; Visser, S.; Speckens, A.E.M.; Batelaan, N.; van Balkom, A.J.L.M.
Abstract : Background: Most patients with noncardiac chest pain experience anxiety and depressive symptoms. Commonly they are reassured and referred back to primary care, leaving them undiagnosed and untreated. Some small studies have suggested efficacy of 12 cognitive behavioral therapy (CBT) sessions. Our aim was to examine efficacy of brief CBT in reducing anxiety and depressive symptoms in patients with noncardiac chest pain and comorbid panic and/or depressive disorders. Methods: In this 24‐week randomized controlled trial comparing CBT (n = 60) versus treatment as usual (TAU, n = 53), we included all adults who presented at the cardiac emergency unit of a university hospital with noncardiac chest pain, scored ≥8 on the hospital anxiety and depression scale (HADS) and were diagnosed with a comorbid panic and/or depressive disorder with the Mini International Neuropsychiatric Interview. CBT consisted of six individual sessions. Main outcome was disease severity assessed with the clinical global inventory (CGI) by a blinded independent rater. Results: ANCOVA in the intention‐to‐treat and completer sample showed that CBT was superior to TAU after 24 weeks in reducing disease severity assessed with CGI (P < .001). Secondary outcomes on anxiety (HADS‐anxiety, state trait anxiety inventory (STAI)‐trait) and depressive symptoms (Hamilton depression rating scale) were in line with these results except for HADS‐depression (P = .10), fear questionnaire (P = .13), and STAI‐state (P = .11). Conclusions: Brief CBT significantly reduces anxiety and depressive symptoms in patients with noncardiac chest pain who are diagnosed with panic and/or depressive disorders. Patients presenting with noncardiac chest pain should be screened for psychopathology and if positive, CBT should be considered.